Metabolic State Determines Sensitivity to Cellular Stress in Huntington Disease: Normalization by Activation of PPARγ - Jin, Youngnam N.; Hwang, Woong Y.; Jo, Chulman; Johnson, Gail V. W. (PLOS ONE, 2012)
Impairments in mitochondria and transcription are important factors in the pathogenesis of Huntington disease (HD), a neurodegenerative disease caused by a polyglutamine expansion in the huntingtin protein. This study investigated the effect of different metabolic states and peroxisome proliferator-activated receptor γ (PPARγ) activation on sensitivity to cellular stressors such as H2O2 or thapsigargin in HD. Striatal precursor cells expressing wild type (STHdhQ7) or mutant huntingtin (STHdhQ111) were prepared in different metabolic conditions (glucose vs. pyruvate). Due to the fact that STHdhQ111 cells exhibit mitochondrial deficits, we expected that in the pyruvate condition, where ATP is generated primarily by the mitochondria, there would be greater differences in cell death between the two cell types compared to the glucose condition. Intriguingly, it was the glucose condition that gave rise to greater differences in cell death. In the glucose condition, thapsigargin treatment resulted in a more rapid loss of mitochondrial membrane potential (ΔΨm), a greater activation of caspases (3, 8, and 9), and a significant increase in superoxide/reactive oxygen species (ROS) in STHdhQ111 compared to STHdhQ7, while both cell types showed similar kinetics of ΔΨm-loss and similar levels of superoxide/ROS in the pyruvate condition. This suggests that bioenergetic deficiencies are not the primary contributor to the enhanced sensitivity of STHdhQ111 cells to stressors compared to the STHdhQ7 cells. PPARγ activation significantly attenuated thapsigargin-induced cell death, concomitant with an inhibition of caspase activation, a delay in ΔΨm loss, and a reduction of superoxide/ROS generation in STHdhQ111 cells. Expression of mutant huntingtin in primary neurons induced superoxide/ROS, an effect that was significantly reduced by constitutively active PPARγ. These results provide significant insight into the bioenergetic disturbances in HD with PPARγ being a potential therapeutic target for HD.